Physician perspectives on the management of viral hepatitis and hepatocellular carcinoma in Myanmar. - Yoona A Kim; Sam Trinh; Si Thura; Khin Pyone Kyi; Thomas Lee; Stan Sze; Adam Richards; Andrew Aronsohn; Grace L H Wong; Yasuhito Tanaka; Geoffrey Dusheiko; Mindie H Nguyen (PLoS ONE)
Background In Myanmar, over five million people are infected with hepatitis B virus (HBV) and hepatitis C virus (HCV). Hepatitis has been a recent focus with the development of a National Strategic Plan on Hepatitis and plans to subsidize HCV treatment. Methods During a two-day national liver disease symposium covering HCV, HBV, hepatocellular (HCC), and end-stage liver disease (ESLD), physician surveys were administered using the automated response system (ARS) to assess physician knowledge, perceptions of barriers to screening and treatment, and proposed solutions. Multivariate logistic regression was used to estimate odds ratio (OR) relating demography and practice factors with higher provider knowledge and improvement. Results One hundred two physicians attending from various specialty areas (31.0% specializing in gastroenterology/hepatology and/or infectious disease) were of mixed gender (46.8% male), were younger than or equal to 40 years old (51.1% 20 to 40 years), had less experience (61.6% with ≤10 years of medical practice), were from the metropolitan area of Yangon (72.1%), and saw <10 liver disease patients per week (74.3%). The majority of physicians were not comfortable with treating or managing patients with liver disease. The post-test scores demonstrated an improvement in liver disease knowledge (9.0% ± 27.0) compared to the baseline pre-test scores; no variables were associated with significant improvement in hepatitis knowledge. Physicians identified the cost of diagnostic blood tests and treatment as the most significant barrier to treatment. Top solutions proposed were universal screening policies (46%), removal of financial barriers for treatment (29%), patient education (14%) and provider education (11%). Conclusions Physician knowledge improved after this symposium, and many other needs were revealed by the physician input on barriers to care and their solutions. These survey results are important in guiding the next steps to improve liver disease management and future medical education efforts in Myanmar.